2006
DOI: 10.4049/jimmunol.176.8.4793
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of NF-κB and NFAT Antagonism by the Forkhead Transcription Factor Foxd1

Abstract: Forkhead transcription factors play critical roles in the maintenance of immune homeostasis. In this study, we demonstrate that this regulation most likely involves intricate interactions between the forkhead family members and inflammatory transcription factors: the forkhead member Foxd1 coordinates the regulation of the activity of two key inflammatory transcription factors, NF-AT and NF-κB, with Foxd1 deficiency resulting in multiorgan, systemic inflammation, exaggerated Th cell-derived cytokine production,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…For example, FOXD1 and FOXD3 TFBSs were identified in genes upregulated by the HPIV1 C mutant viruses. Only recently has an important role for FoxD1 in the regulation of immune activation through the NF-B pathway been identified (42). FoxD3 is well known for controlling cellular differentiation, but no role for FoxD3 in the regulation of the immune response or the response to viral infection has yet been defined.…”
Section: F170smentioning
confidence: 99%
“…For example, FOXD1 and FOXD3 TFBSs were identified in genes upregulated by the HPIV1 C mutant viruses. Only recently has an important role for FoxD1 in the regulation of immune activation through the NF-B pathway been identified (42). FoxD3 is well known for controlling cellular differentiation, but no role for FoxD3 in the regulation of the immune response or the response to viral infection has yet been defined.…”
Section: F170smentioning
confidence: 99%
“…Studies in model organisms such as Caenorhabditis elegans, Drosophila melanogaster, and Mus musculus have demonstrated a pivotal role for Fox family transcription factors in embryonic patterning, development, and metabolism (1). Recent elucidation of roles for this family of transcriptional regulators in thymic development (Foxn1), lineage commitment (Foxp3), and function of lymphocytes (Foxj1, Foxo3, and Foxd1) has firmly established a role for this transcription factor family in the development and maintenance of normal immune responses (2,3).…”
Section: T He Forkhead (Fkh)mentioning
confidence: 99%
“…Mariani & Harland (1998) showed that Xbf2 is a transcriptional repressor that could convert ectoderm into neural tissue. In addition, Foxd1 can mod- ulate inflammatory reactions and prevents autoimmunity by directly regulating anti-inflammatory regulators of the NF-AT (nuclear factor of activated T cells) pathway and by coordinating the suppression of the NF-κB (nuclear factor kappa B) pathway via Foxj1 (Lin & Peng 2006). At present, much attention was paid to the function of FoxD1 in kidney and neural development in higher vertebrates, but its function in muscle development, derivative of mesoderm, especially in fish species, is poorly understood.…”
Section: Introductionmentioning
confidence: 99%